EVALUATION OF THE DISABILITY-FRIENDLY EDUCATION MANAGEMENT MODEL IN ELEMENTARY SCHOOLS - Dacholfany, Muhammad Ihsan; Rahmi, Hanifatul; Tira, Deviarbi Sakke (PT Altin Riset Publishing, 2023)
The goal will be achieved in the study. This is the Management Model Evaluation Disability-Friendly Education in Schools Basic. Methods used in the study This is a method study qualitative as for the type of research used, i.e., the usage studies case, because the researcher can understand in a way the deep context, process, and complexity of the phenomenon researched. Results study This explain If creating a disability-friendly and disability-friendly educational environment at the primary school level is essential to providing a strong foundation for the development of children with disabilities, the Disability-Friendly Education Management model in State Primary Schools in Lampung is an inclusive approach that aims to provide equal and meaningful education for all students, including those with special needs. Through inclusive curriculum development, intensive teacher training, partnerships with parents, disability-friendly infrastructure, and special support for students with disabilities, these schools create inclusive environments that enable all students to reach their optimal potential.